Diazotrophic bacteria increase yield and profitability in organic cultivation of common bean - Martins, Juliana T. [UNESP]; Buzo, Fernando de S. [UNESP]; Garé, Lucas M. [UNESP]; Garcia, Nayara F. S. [UNESP]; Sales, Letícia Z. de S. [UNESP]; Do Nascimento, Matheus V. L. [UNESP]; Dos Santos, Neli C. B.; Sabbag, Omar J. [UNESP]; Arf, Orivaldo [UNESP] (FapUNIFESP (SciELO), 2024)
The symbiosis of common beans with nitrogen-fixing bacteria provides an efficient approach to sustainable and economical food production. Therefore, this study aimed to evaluate the application of cost-effective nitrogen management strategies in organic common bean cultivation, including the application of poultry manure and organic liquid fertilizer, seed and co-inoculation with diazotrophic bacteria (Azospirillum brasilense and/or Rhizobium tropici), and supplementary Rhizobium tropici inoculation. The study spanned three years in a well-established organic cultivation field (2018) and an initial organic cultivation area (2019 and 2020) in Brazil. It was arranged in a randomized blocks design in a 2 × 5 (2018) and 2 × 6 (2019 and 2020) factorial scheme, with four replicates. The most profitable strategy involves seed inoculation with Azospirillum brasilense and additional inoculation with Rhizobium tropici at stage V4-5 (fifth trifoliate leaf fully expanded), while the most costly strategy was the application of poultry manure at the V3 stage (first trifoliate leaf fully expanded). Thus, the use of diazotrophic bacteria for seed inoculation and co-inoculation (Azospirillum brasilense and/or Rhizobium tropici) ensured financial returns and system profitability in common bean cultivation.
Bactérias diazotróficas aumentam produtividade e rentabilidade no cultivo orgânico do feijão comum
Keywords: Azospirillum brasilense; economic performance; Phaseolus vulgaris L; Rhizobium tropici